The Concept of Ịgbandụ in Nnewi, Anambra State, Nigeria: A Discourse Analysis - Agbasianya, Maria Nneka; Uroko, Favour C. (Journal Of Spirituality And Practical Theology, 2025)
Religious practices and the adoption of Christianity absorbed and replaced a great deal of previous traditional practices, but some remained. This study examined how the arrival of Christianity affected the practice of Igbandu in Nnewi. Igbandu in Nnewi is about people using blood, oil, salt, hot drinks, kola nuts, etc. to make covenants. This study is hinged on the observation that although attempts have been made to explore the resilience of Igbo cultural practices in spite of the impact of Christianity, there is a dearth of studies on the resilience of Igbandu, especially case studies dealing with specific localities. Existing literature has not adequately explored the impact of Christianity on the concept of Igbandu, precisely in Nnewi. In this study, the literature was extended to investigate the phenomenon of Igbandu in Nnewi. This is a qualitative study that adopted a phenomenological design. It also made use of historical and sociological approaches to examine the different dimensions of the impact. Data was collected from primary and secondary sources and analysed descriptively. Some informants were selected purposefully due to their knowledge about the phenomenon of Igbandu in Nnewi. It was found that Igbandu was not affected by Christianity but rather adopted Christian practices. It was largely due to the understanding that Igbandu promoted transparency, truth, and togetherness more than it discouraged them. Additionally, conventional religious analysts have focused on the harmful effects of certain traditional practices, arguing that their adoption into Christian practices nullifies what they preach as Christians, which is that light and darkness cannot coexist together. The issue with this perspective, however, is that it ignores the role Igbandu has played in shaping our culture and traditions. Conclusively, the positive impacts of Igbandu have made people more transparent and accountable to one another and promoted togetherness